People in Corporations
VIII, 264 p.
Keywords: Georges Enderle Before presenting some introductory remarks on the topic of this volume I should like to outline briefly the context from which this selection of articles originates. (It seems to me necessary to emphasise these circumstances in order to make clearer the contours of what is said and what is not said and to understand it better. ) This context involves, flrstly, a general evaluation of the state of the business ethics debate today and, secondly, considerations of the question of what attitude and strategy should be chosen in order to promote business ethics most effectively. On the present state of affairs of the business ethics debate Today, it is extremely difflcult, if not impossible, to gain even a rough overview of the business ethics debate in the different countries of Europe and North America. Many activities take place in informal circles and on a local and regional level; linguistic and other barriers impede the spread of information about them and, often, they are not even labelled "business ethics". At the same time, so many other things sail under the flag of "business ethics" that one sometimes wonders if it should not be replaced by another flag, for instance new methods of public-relations or better motivation of company's employees. Yet, in spite of these difflculties in deflning business ethics activities, one statement at least can be made with certainty. .